A rare case of gastric carcinoid presenting as subacute combined degeneration of spinal cord - Sharma, Abhishek; Gowtham, Gowtham; Nawal, C.L.; Agarwal, M.K.; Chejara, R.S. (International Journal of Medical Research and Review, 2016)
Gastric carcinoids originate from the foregut and are derived from enterochromaffin-like (ECL) cells, which are the main neuroendocrine cells in the gastric mucosa. Gastrin acts directly on ECL cells to induce hyperplasia, dysplasia, and, eventually, neoplasia or carcinoid . In patients with chronic atrophic gastritis, decreased gastric acid secretion stimulates the secretion of gastrin, and ECL cells transform into a carcinoid. Herein we report a case of type I gastric carcinoid presenting as SACD.